2004
DOI: 10.1021/bi035802w
|View full text |Cite
|
Sign up to set email alerts
|

Transferrin-Modified Liposomes Equipped with a pH-Sensitive Fusogenic Peptide:  An Artificial Viral-like Delivery System

Abstract: Liposomes are one of the most promising systems for selective cellular targeting via introduction of specific ligands for cell-surface receptors. After being taken up by the cells, these liposomes usually follow intracellular pathways of receptor-mediated endocytosis. Control of intracellular trafficking is required for optimized drug delivery. In this study, we elucidated the intracellular fate of transferrin-modified liposomes and succeeded in altering it by introducing the pH-sensitive fusogenic peptide, GA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
164
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 268 publications
(168 citation statements)
references
References 26 publications
3
164
1
Order By: Relevance
“…Coencapsulation of a fusogenic peptide derived from the influenza virus hemagglutinin resulted in efficient cytosolic delivery of liposomal diphtheria toxin A-chain as reported by Mastrobattista et al (9). Kakuda et al demonstrated that the insertion of cholesterol derivatized GALA-peptide into the liposomal bilayer also stimulated release of liposomal contents into the cytosol (10).…”
Section: Introductionmentioning
confidence: 81%
“…Coencapsulation of a fusogenic peptide derived from the influenza virus hemagglutinin resulted in efficient cytosolic delivery of liposomal diphtheria toxin A-chain as reported by Mastrobattista et al (9). Kakuda et al demonstrated that the insertion of cholesterol derivatized GALA-peptide into the liposomal bilayer also stimulated release of liposomal contents into the cytosol (10).…”
Section: Introductionmentioning
confidence: 81%
“…Similar observations were made previously regarding the impact of the topology of the fusogenic peptide GALA on endosomal escape. 7 Thus, the topology and content of a lipid envelope significantly influence both particle uptake and the function of devices embedded in the envelope. Although the diameters of MENDs1-3 were somewhat different (Supplementary Table 1 online), it is suggested that this difference has no significant effect on the uptake pathway of the particles.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 A variety of approaches have been used to overcome these barriers including ligandmediated targeting of cell surface receptors, pH-sensitive fusogenic peptides that improve cytosolic delivery and nuclear localization signals (NLSs) to enhance nuclear uptake. [6][7][8][9] Many of the currently available non-viral vectors have some functional devices that enhance their overall efficiency; however, they are still much less efficient than most viral vectors, 10 which evolved towards, maximum efficiency through the process of natural selection. Simple mixing of DNA with multiple devices does not guarantee that each device is functional and effective in reducing barriers to efficient gene delivery.…”
Section: Introductionmentioning
confidence: 99%
“…134 GALA enhanced cytosolic release of a fluid phase marker cointernalized with Tf-targeted liposomes compared to complexes lacking GALA. 135 While these particular studies did not examine DNA delivery by these complexes, they demonstrate that modified GALA, synthesized to attach to the surface of liposomes, undergoes pH-dependent conformational changes consistent with a-helix formation, and induces membrane fusion.…”
Section: Endosomolysismentioning
confidence: 99%